2015
DOI: 10.5937/ffr1502092r
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-amylase activity in wheat flour and breadmaking properties in relation to different climatic conditions

Abstract: ABSTRACT:The aim of the present paper was to evaluate the influence of different climatic conditions on the activity of alpha-amylase in wheat samples and bread quality parameters. Three wheat varieties grown in three different localities in three years were chosen for this study. Commonly used methods for estimation of alpha-amylase activity in wheat grain were employed. The obtained results indicated that harvest year 2013, which was characterized with the excessive amount of rainfall, exhibited the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…On the other hand, the high temperature resulted in significantly lower enzyme activity in grains grown in Gladebeck, compared to those in Torland during the later ripening stages (Figures 1 and 2). Similar results were reported from previous studies showing that wheat grains had significantly lower α‐amylase activity when exposed to temperatures ≥30 °C, compared to 10–13 °C, [ 5,12,46 ] either during grain development or before harvest. [ 10 ] Biddulph et al.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…On the other hand, the high temperature resulted in significantly lower enzyme activity in grains grown in Gladebeck, compared to those in Torland during the later ripening stages (Figures 1 and 2). Similar results were reported from previous studies showing that wheat grains had significantly lower α‐amylase activity when exposed to temperatures ≥30 °C, compared to 10–13 °C, [ 5,12,46 ] either during grain development or before harvest. [ 10 ] Biddulph et al.…”
Section: Discussionsupporting
confidence: 90%
“…[ 2 ] Furthermore, the protein of α‐amylase belongs to albumin and globulin fractions, the latter accounting for 90% of the total proteins during the first two weeks of grain growth, and then decreases until it accounts for 20–30% in the stage of full ripeness, [ 8,38 ] so it can be assumed that α‐amylase activity is somehow correlated with protein content as has been stated in several studies. [ 12,39,40 ] In our study, a strong significant correlation was observed between the α‐amylase activity of wheat and the protein during grain ripening (Tables 4 and 5).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It is well known that alpha-amylase has notable influence on wheat flour processing and bread production, and hence a certain level of this enzyme is desirable to achieve the optimal quality properties of baked products, while excess alpha-amylase has a detrimental effect on baked bread. Although AA was higher in year 3 than in years 1 and 2, the level of alpha-amylase activity was not sufficiently elevated to cause changes in the wheat flour and deteriorate the wheat processing quality, which was confirmed in a preliminary study [32]. Moreover, the level of alpha-amylase activity remained within the optimal level for bread-making, which was confirmed by the baking test showing no impairment in the end-use quality characteristics [33].…”
Section: Discussionmentioning
confidence: 61%